Curtailed T‐cell activation curbs effector differentiation and generates CD8+ T cells with a naturally‐occurring memory stem cell phenotype. Issue 9 (28th July 2017) - Zanon, Veronica; Pilipow, Karolina; Scamardella, Eloise; De Paoli, Federica; De Simone, Gabriele; Price, David A.; Martinez Usatorre, Amaia; Romero, Pedro; Mavilio, Domenico; Roberto, Alessandra; Lugli, Enrico
Abstract : T memory stem cells (TSCM) with increased persistence are most suitable cell type for adoptive cell transfer immunotherapy. Weak TCR stimulation of human naïve CD8+ T cells induces a CD45RO– CD45RA+ TSCM phenotype. The proliferating TSCM display decreased T‐cell activation, effector molecules and mitochondrial content compared to more differentiated T effectors. Abstract: Human T memory stem (TSCM ) cells with superior persistence capacity and effector functions are emerging as important players in the maintenance of long‐lived T‐cell memory and are thus considered an attractive population to be used in adoptive transfer‐based immunotherapy of cancer. However, the molecular signals regulating their generation remain poorly defined. Here we show that curtailed T‐cell receptor stimulation curbs human effector CD8 + T‐cell differentiation and allows the generation of CD45RO – CD45RA + CCR7 + CD27 + CD95 + ‐phenotype cells from highly purified naïve T‐cell precursors, resembling naturally‐occurring human TSCM . These cells proliferate extensively in vitro and in vivo, express low amounts of effector‐associated genes and transcription factors and undergo considerable self‐renewal in response to IL‐15 while retaining effector differentiation potential. Such a phenotype is associated with a lower number of mitochondria compared to highly‐activated effector T cells committed to terminal differentiation. These results shed light on the molecular signals that are required to generate long‐lived memory T cells with potential application in adoptive cell transfer immunotherapy.